Risk Factors of Depression among Women Living in Rural Areas of Iranshahr, Iran - Rajabi , Azam; Salari , Fateme; Aghasi, Majid (Shahroud Journal of Medical Sciences, 2021)
Background: Depression is one of the most common mental problems which is not limited to a certain location or time, afflicting various social and age groups. This study aimed to examine factors affecting depression among women in rural areas.Methods: This study was conducted on an Iranian population residing in rural areas of Iranshahr. The research population comprised all women in rural areas of Iranshahr. Using systematic random sampling, about 6% of the 666 covered villages were selected. Using Goldberg’s standard questionnaire, the data on blood glucose, physical activity, height, weight, and blood pressure were collected using interviews and measurement and analyzed via correlation test and chi-squared test.Results: In this study, a correlation existed between depression factors and blood pressure, physical activity, blood glucose, economic and family problems of female householders (Pvalue<0.05).Conclusions: One of the best solutions for preventing depression in women in rural areas is strengthening their economic status. By predicting depression, the emergence of many physical diseases and disorders such as hypertension and high blood glucose can be prevented beyond expectations.Keywords: Rural women; Risk factors; Depression; Iranshahr